Efeitos da oxigenoterapia hiperbárica em parâmetros hematológicos, lactatemia e hemogasometria de gatas submetidas à ovariohisterectomia eletiva videoassistida - Fischborn, Nadine Trinks (2021)
Hyperbaric oxygen therapy has emerged as a therapeutic modality in the management of several acute and chronic conditions, both in human and veterinary medicine. Its application leads to tissue hyperoxygenation, immunomodulation and reduction of oxidative stress in humans. The elective ovariohysterectomy (OHE) is one of the most common surgical procedures performed in the small animal clinic, and has a role both in preventing mating and various conditions. There are different techniques for the execution of minimally invasive OHE, with emphasis on the video-assisted approach. There are no records in literature of physiological changes in cats undergoing hyperbaric oxygen therapy. This study aimed to evaluate the consequences of using oxygen therapy in a hyperbaric chamber in cats in the preoperative period of video-assisted ovariohysterectomy with two portals, in addition to assess its influence on blood gas analysis, lactatemia and blood cell count. Cats were separated into three groups to analyse these effects, namely: Sham Group (GS), Hyperbaric Group (GH) and Hyperbaric Control Group (GHC). Hematological, lactatemia and venous blood gas analysis was performed. It was concluded that there is no significant influence of pre-treatment with HBOT on parameters such as base excess in healthy cats. HBOT can lead to an increase in serum lactate in cats and a decrease in pH, without necessarily causing metabolic acidosis. There is a positive influence of HBOT in pO2 and pCO2 values. There may be a drop in the hematocrit, red blood cells and hemoglobin values, and it is recommended to carry out a control blood count before the session. Leukocytosis with neutrophilia and lymphopenia can be expected..